CYCLE LENGTH CHANGES OF THE SRd VARIABLE UU HER? - Pikhun, A. I.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
Best fit periods for individual seasons show variations from 27d to 101d with a possible cycle ≈ 5500d. One - and multi- frequency sine approximations of 650 photovisual observations argue for a formal 2 component model with periods P1 = 44.92 ± .06d, P2 = 70.37 ± .16d and semi-amplitudes r1 = 0.093 ± .010m, r2 = 0.086 ±.009m.